Concise Dictionary of American biography. - American Council of Learned Societies. Committee on the Dictionary of American Biography; American Council of Learned Societies. Committee on the Dictionary of American Biography (New York : Charles Scribner's Sons, 1964)
This one-volume abridgment of the Dictionary of American biography includes the 14,870 entries of the parent work in reduced form. Coverage is limited to persons no longer living and includes "explorers, frontiersmen, artists and scientists, craftsmen, inventors, businessmen, surgeons and physicians, feminists, scholars, politicians and statesmen"--Publisher's note.
Keywords: Biographies as Topic; United States -- Biography -- Dictionaries; Dictionary; Biography; dictionaries; Biographies; Dictionaries